PENGARUH BUDAYA ORGANISASI DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA BANK INDONESIA PROVINSI KALIMANTAN BARAT - B31111136, ARIF WIBOWO (Jurnal Manajemen Update, 2017)
This study aims to determine how the influence of organizational culture and discipline the performance of employees at Bank Indonesia Representative Office in West Kalimantan. The study uses research methods Causal research with qualitative and quantitative approaches. Collecting data using primary and secondary data obtained by distributing questionnaires in Bank Indonesia province of West Kalimantan. The sample in this study using the census sampling, with a sample of 40 people who are employees of the Bank Indonesia province of West Kalimantan. Results from the study showed that the organizational culture and discipline significantly influence performance Employees of Bank Indonesia Province Of West Kalimantan. Keywords: Organizational Culture, Discipline and Employee Performance